Political Interests and Their Impact on US-China Competition in the South China Sea Region During 2009-2023 - Alheari, Ahmad Samir Ahmad (Dirasat: Human and Social Sciences, 2025)
Objectives: To elucidate the nature of border disputes among countries in the South China Sea region, American and Chinese interests, and the dimensions of US-China competition in the area. Methods: The study employed the national interest approach alongside descriptive and analytical methodologies to accomplish its objectives and address its inquiries. Results: The South China Sea has emerged as a focal point for competition between China and the United States, propelled by their strategic interests. The competition between the two nations revolves around geopolitical control of the South China Sea, encompassing military, security, and political dimensions. China has bolstered its military capabilities and expanded its control over South China Sea islands. Conversely, the United States has escalated its military presence in the region to safeguard its interests and fulfill security commitments to regional allies. Conclusions: The study underscores the significance of the United States fortifying its strategic ties with South China Sea nations to uphold its military supremacy and sustain a regional balance of power in its favor.